Gambaran Kondisi Lingkungan dan Kualitas Air Bersih Rumah Balita Stunting di Kabupaten Kediri: Pengabdian - Lilis Sulistyorini; R.Azizah; Novi Dian Arfiani; J.Mukono; Soedjajadi Keman; Ririh Yudhastuti; Sudarmaji; Retno Adriyani; Corie Indria Prasasti; Muhammad Farid Dimjati Lusno; Kusuma Scorpia Lestari; Khuliyah Candraning Diyanah; Aditya Sukma Pawitra; Zida Husnina; Ratna Dwi Puji Astuti; Ratnaningtyas Wahyu Kusuma Wardani; Endang Dwiyanti; Hana’ Izdihar; Avita Fitri Agustin; Yulfa Tiara Kencana (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Indonesia has the third highest prevalence of stunting in Southeast Asia. One of the main factors is poor environmental hygiene and sanitation, which causes infections and impaired nutrient absorption in children under five. Inadequate sanitation and poor water quality increase the risk of stunting. In Silir Village, Wates Sub-district, there were 18 cases of stunting in December 2023. To address this, a holistic approach is needed, including the implementation of the 5 Pillars of Community-Based Total Sanitation (STBM). The community service was conducted in three stages: preparation, implementation, and evaluation. Activities included water quality checks (all water samples contained E.coli), hygiene education, sanitation inspections, and assistance with water, waste, and liquid waste management. Education related to stunting and environmental conditions was conducted, along with a pre-test and post-test that showed an increase in the average score from 69.9 to 73.1. Further intervention is needed to improve the bacteriological quality of drinking water in the homes of stunted toddlers in Silir Village.